The SIM Registration Legislation in Enhancing Mobile Security against Cyber Threats - Tumang, Bryan John (Future Science / FSH-PH Publications, 2025)
ABSTRACT The SIM Card Registration Act has been actively advocated by the Department of Information and Communications Technology (DICT), aiming to raise awareness and encourage individuals to register their SIM cards. In addition, the DICT has been working closely with tele-communications companies to enhance the efficiency and simplicity of the registration procedure. Undoubtedly, the implementation of the SIM Card Registration Act plays a pivotal role in establishing a safer and more secure environment in the Philippines. The research aims to investigate and analyze the impact of SIM registration legislation as a regulatory mechanism in enhancing mobile security against cyber threats. More specifically, the study will seek Strengths and weak-nesses of SIM registration legislation in addressing challenges in mo-bile security.The study will be conducted in the District 2 Manila, Philippines with an estimated population of 212,938 (manila.gov.ph). The re-spondents will be interview and answering a survey questionnaire in their houses or any comfortable place that the respondent will choose or the respondents may answer the survey questionnaire via Google form. The study employed a purposive sampling scheme in which re-spondents were purposefully chosen by the researcher that targets a group of people that have been affected by mobile phone-related crimes, law enforcement officials, legal experts, policymakers, or oth-er stakeholders directly involved in the enforcement of RA 11934.The main instrument will be use of the researchers in gathering the data for this study was self- made questionnaire which is con-structed after analyzing literatures and studies related to the present study.The results revealed the implementation of the SIM Registration Act has had significant implications for various cyber threats, includ-ing swindling / estafa, identity theft, and terrorism. By mandating the registration of SIM cards, authorities aim to enhance accountability and traceability in communication networks. The flaws within SIM registration systems contribute to the emergence of a black market for registered SIM cards. This illicit market enables their utilization in criminal activities, thereby undermining the intended security bene-fits that the registration process aims to provide.